Bridging the Peace: Assessing Cultural-Linguistic Competence in the Mission Effectiveness of the Garuda Contingent - Budi Achmadi; Togap Marlon Siburian; Indra Kristian (The International Journal of Law Review and State Administration, 2026)
UN peacekeeping operations in multinational and multicultural environments demand adaptative intercultural capacities from military personnel. This study aims to analyze the influence of foreign language proficiency specifically comprehension skills (listening/reading) and delivery skills (speaking/writing) on the mission effectiveness of the Garuda Contingent in World Peacekeeping Operations. Utilizing a mixed-methods approach, quantitative data were gathered through surveys distributed to Garuda Contingent personnel, while qualitative data were obtained via in-depth interviews detailing operational barriers and adaptation strategies. Regression analysis results indicate that both comprehension and delivery skills have a positive and significant impact on mission success. The quantitative model demonstrates a highly robust contribution, revealing that 90.3% of the variance in operational task success can be explained by these two language proficiency variables. Qualitatively, language mastery is significantly driven by individual motivation, prior deployment experience, training intensity, and workplace environmental support. On the ground, tactical communication barriers are mitigated through intercultural adaptation strategies, such as linguistic simplification, interpreter assistance, message reiteration, and cultural engagement. This study concludes that foreign language competence is a strategic imperative rather than a mere secondary skill. Practically, it implies an urgent need to restructure language training programs into more sustainable, contextualized frameworks tailored to the geopolitical dynamics of the specific mission area.